Hybridization of two Southern appalachian blueberry species with rabbiteye and southern highbush blueberry. - RITZINGER, R. (1997)
Introduction; Crossing experiments; Self-fruitfulness and self-fertility; Open-pollinated fertility; Fruit quality; Flower morphology; Pollen fertility and unreduced gametes; Leafing and flowering; Flowering and ripening time